A prospective randomized half-body study: 308 nm LED light vs. 308 nm excimer laser for localized psoriasis - Yu, Yingyuan; Lu, Jiajing; Zhang, Yi; Shi, Yuling (Frontiers in Medicine, 2023)
Background Psoriasis is a chronic skin disease affecting approximately 3.2% of the population. The 308 nm light emitting diode (LED) is a novel, portable, and cost-effective light source, may have potential in the treatment of localized psoriasis patients in a home setting. Objective To compare the clinical and dermoscopic responses in localized psoriatic patients undergoing localized phototherapy with 308 nm LED light and excimer laser. Methods Twenty-two patients with mild-to-moderate psoriasis and symmetrical skin lesions were included in this prospective, randomized, left-to-right body trial. The target lesions were randomly treated with either LED light or excimer laser twice a week for 12 weeks. The responses were evaluated by the local psoriasis severity index (LPSI) scores, and dermoscopic features of the target lesions were examined and analyzed. Results Out of the 22 included psoriasis patients, 10 successfully completed the 12 weeks study. Both treatment sides showed similar clinical improvement in terms of clinical response, as evidenced by a LPSI 50 rate of 70% on the LED side and 80% on the excimer side, p > 0.05. Furthermore, the dermoscopic features also exhibited comparable improvement. Conclusion The efficacy and safety of 308 nm LED light therapy are comparable to 308 nm excimer laser therapy. Moreover, given the portability and cost-effectiveness of 308 nm LED light, it holds great promise as a home phototherapy in the treatment of psoriasis.